Heterochrony and evolution in some Toarcian ammonites. Speculations and insights - Ridente, Domenico (Journal of Mediterranean Earth Sciences, 2016)
The record of Hildoceras species from the Rosso Ammonitico marls (Toarcian) near Terni (Central Apennines) is analysed in order to outline a possible relationship between ontogenetic and phylogenetic variability. Bed by bed sampling provides evidence of ontogenetic variability in shell morphology that parallels evolutionary change, suggesting a possible control by heterochrony. Specifically, heterochrony is proposed as a potential mechanism by which: 1) discontinuous inflections accompanying rib fading at the inner flank of Hildoceras lusitanicum, initially a character of later growth stages, are progressively anticipated during ontogeny, finally culminating in the spiral groove of Hildoceras bifrons; 2) delayed maturation and inhibition of the adult "uncoiling" stage of Hildoceras bifrons, concomitant to allometric growth of whorl height, result in the overall involute and relatively compressed shell structure observed in Hildoceras semipolitum. Interrelated to heterochrony is also the concept of "developmental polymorphism", considered as a plausible alternative and more general frame in which to place sexual dimorphism as displayed by Hildoceras bifrons.